2009
DOI: 10.1093/annonc/mdp263
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of discordance between triple-receptor measurements in primary and recurrent breast cancer

Abstract: Concordance of quantitative hormone receptor measurements between primary and recurrent tumors is modest consistent with suboptimal reproducibility of measurement methods, particularly for IHC. Discordant cases have poor survival probably due to inappropriate use of targeted therapies. However, biological change in clinical phenotype cannot be completely excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
203
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(220 citation statements)
references
References 20 publications
17
203
0
Order By: Relevance
“…Moreover, we report here for the first time a statistically significant correlation between previous systemic treatments and modifications in receptors' expression. Several studies have addressed the issue of concordance/ discordance in receptors expression between primary tumor and metastases [9,[12][13][14][15][16][17][18][19][20][21][22][23][24]. Published studies have found discordance rates for ER status ranging from 10.2% to 56%, PR status ranging from 24.8% to 48.6%, and HER2 status ranging from 2.9% to 16%.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we report here for the first time a statistically significant correlation between previous systemic treatments and modifications in receptors' expression. Several studies have addressed the issue of concordance/ discordance in receptors expression between primary tumor and metastases [9,[12][13][14][15][16][17][18][19][20][21][22][23][24]. Published studies have found discordance rates for ER status ranging from 10.2% to 56%, PR status ranging from 24.8% to 48.6%, and HER2 status ranging from 2.9% to 16%.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the discordance in HER2 status between primary tumor and recurrence vary from 50% (in CTC) down to 6% [7][8][9][10][16][17][18]. However the data from studies based on CTC cannot be compared with standard morphological methods.…”
Section: Discussionmentioning
confidence: 99%
“…A large retrospective study of triple negative disease, based on 789 patients, showed intra-individual discordance regarding HER2 status of 13.6% [9]. One study showed good correlation (97%) in HER2 status between primary breast cancer and circulating tumor cells, collected at the same time point.…”
Section: Introductionmentioning
confidence: 99%
“…Only full published papers were included because the study required detail on the number of changes in receptor status. Of multiple articles published from the same institution, only the article with the largest sample size was chosen (e.g., of the two studies from University of Texas MD Anderson Cancer Center [4,16], we used the later study [4]). If necessary, we e-mailed the authors of studies for additional data needed for the metaanalysis.…”
Section: Meta-analysis Of Primary Tumors and Metastatic Lesionsmentioning
confidence: 99%